A DIGITAL SOLUTIONS FOR AGRICULTURE: BUILDING A DEMAND AND SUPPLY (D&S) PORTAL FOR MONITORING AGRICULTURAL PRODUCTS (Journal of Digital System Development, 2023)
This study addresses these challenges by exploring the issues faced by the agriculture industry, particularly the need for marketing information, difficulties in reaching potential purchasers, and the need for effective marketing strategies. However, effectively managing this sector's complex supply and demand dynamics presents substantial challenges. The primary objective of this research is to develop a user-friendly agriculture portal called a Demand and Supply (D&S) Portal that empowers small-scale farmers to make informed decisions about marketing their products. The Agile methodology guides the development of this portal, ensuring flexibility, adaptability, and iterative development. The research process incorporates rigorous literature reviews and problem recognition as foundational steps before system development. The evaluation of the portal indicates high user satisfaction. Respondents found the portal's features for managing and monitoring agricultural product demand and supply straightforward and valuable. The portal's usability and efficiency were well-received, with users expressing their intention to recommend it to others. It serves as a reference model for developers and researchers in the agricultural sector, offering valuable insights into demand and supply management. Future enhancements include optimising the portal for mobile use, incorporating product images and pricing information, and enhancing security features. The D&S Agri Portal is a promising tool for empowering small-scale farmers and improving the efficiency of agricultural transactions. Continuous user feedback and technological adaptations will enhance its usability and effectiveness in facilitating agricultural demand and supply management. This research contributes to understanding the agriculture industry's challenges and the potential solutions to address them. It also highlights the importance of empowering small-scale rural farmers through effective marketing platforms.